Salmonella spp. in Horses with Diarrhea: Clinical, Laboratory and Microbiological Aspects - Hellen Vieira da Cunha, Neri; Moreira Cerri, Fabrício; Martins Basso, Roberta; Oliveira da Silva, Thayná; Laufer-Amorim, Renée; García Ribeiro, Márcio; Stachewski Zakia, Luiza; Adriano Biscola Pereira, Wanderson; Paes Oliveira-Filho, José; Alexandre Secorun Borges; et al. (Acta Scientiae Veterinariae, 2026)
Background: Salmonellosis is an important cause of diarrhea in horses with zoonotic implications. Diagnosis depends on the isolation of the agent through serial cultures or molecular techniques. The aim of this retrospective study was to describe the clinical, laboratory, and microbiological aspects of salmonellosis in horses presenting diarrhea referred to a veterinary teaching hospital. Materials, Methods & Results: Horses presenting signs of diarrhea treated between January 2009 and December 2019, from which Salmonella spp. were isolated from feces, were included in this study. Epidemiological data, clinical and laboratory findings (hematology, serum biochemistry, and blood gas analysis), and in vitro antimicrobial resistance profiles were analyzed. During this period, 78 of the admitted horses presented diarrhea, and Salmonella spp. were isolated from 28% (22/78) of them. Among these patients, 41% (9/22) were younger than 3 months, 27% (6/22) were between 6 and 12 months, 14% (3/22) were between 2 and 7 years, and 18% (4/22) were older than 9 years. Clinical signs included tachycardia, tachypnea, mucous membrane congestion and liquid feces. Clinicopathological tests revealed hyperfibrinogenemia, increased gamma-glutamyl transferase serum activity and metabolic acidosis. In addition to feces, Salmonella spp. were isolated from 10% (2/22) and 5% (1/22) of lung and intestinal tissues and blood, respectively, from horses that did not survive. The isolates were resistant to sulfamethoxazole/trimethoprim (4/20; 20%) and gentamicin (3/20; 15%), along with partially resistant strains (5/20; 25%) and strains resistant (2/20; 10%) to ceftiofur. The mortality rate in the study population was 59%. Discussion: The study highlights the severe impact of equine salmonellosis, particularly in cases complicated by septic shock, which contributed to a high mortality rate and limited the assessment of hospitalization duration and prognosis. The confirmed etiology of diarrhea was based on the isolation of Salmonella spp. through fecal, tissue, and blood cultures, with systemic dissemination evident in some cases. Serial fecal culture remains the diagnostic gold standard, although a single positive sample can suffice in horses with gastrointestinal symptoms. The antimicrobial resistance profile revealed significant resistance to sulfamethoxazole/trimethoprim, gentamicin, and ceftiofur. Notably, some isolates were partially sensitive (25%) or resistant (10%) to ceftiofur, reflecting concerns about the future efficacy of cephalosporins due to their widespread use in veterinary medicine. However, the absence of multidrug-resistant strains in this study contrasts with findings from other species and age groups, suggesting that antimicrobial use practices and regulatory differences may influence resistance patterns. Necropsy findings were consistent with equine salmonellosis and bacterial enterocolitis, indicating loss of intestinal barrier integrity, bacterial dissemination, and sepsis development. These findings underline the importance of early diagnosis, effective antimicrobial stewardship, and a better understanding of resistance mechanisms to improve outcomes in equine salmonellosis cases. This study confirms that salmonellosis is a prevalent cause of enterocolitis in horses and is responsible for a high mortality rate. We emphasize the importance of evaluating the antimicrobial susceptibility profile in all cases. Keywords: equines, diarrhea, nosocomial infection, antimicrobial susceptibility, sepsis, colitis.